Intrapartum Ultrasound Assessment of Fetal Spine Position. (3rd August 2014) - Gizzo, Salvatore; Andrisani, Alessandra; Noventa, Marco; Burul, Giorgia; Di Gangi, Stefania; Anis, Omar; Ancona, Emanuele; D'Antona, Donato; Nardelli, Giovanni Battista; Ambrosini, Guido
Abstract : We investigated the role of foetal spine position in the first and second labour stages to determine the probability of OPP detection at birth and the related obstetrical implications. We conducted an observational-longitudinal cohort study on uncomplicated cephalic single foetus pregnant women at term. We evaluated the accuracy of ultrasound in predicting occiput position at birth, influence of fetal spine in occiput position during labour, labour trend, analgesia request, type of delivery, and indication to CS. The accuracy of the foetal spinal position to predict the occiput position at birth was high at the first labour stage. At the second labour stage, CS (40.3%) and operative vaginal deliveries (23.9%) occurred more frequently in OPP than in occiput anterior position (7% and 15.2%, resp.), especially in cases of the posterior spine. In concordant posterior positions labour length was greater than other ones, and analgesia request rate was 64.1% versus 14.7% for all the others. The assessment of spinal position could be useful in obstetrical management and counselling, both before and during labour. The detection of spinal position, more than OPP, is predictive of successful delivery. In concordant posterior positions, the labour length, analgesia request, operative delivery, and caesarean section rate are higher than in the other combination.